BED OCCUPANCY RATE AND LENGTH OF STAY OF PATIENTS IN MEDICAL AND ALLIED WARDS OF A TERTIARY CARE HOSPITAL - Usman, Gulzar; Memon, Khalida Naz; Shaikh, Shazia (Journal of Ayub Medical College Abbottabad, 2015)
Background: A good hospital management includes an effective allocative planning for beds in a hospital. Bed-occupancy rates and length of stay are the measures that reflect the functional ability of a hospital. Methods: A cross sectional study of two months’ duration was carried out in eight medical and allied wards of Liaquat University Hospital (LUH) Jamshoro with objective to estimate the bed occupancy rate and the average length of stay of patients. Data was collected by filling a pre-designed check list and bed occupancy rate and average length of stay were computed. Associations were analysed by using SPSS version 16. The p-value ‰¤0.05 was taken as level of significance. Results: One hundred & seven admissions were recorded against 235 available beds. Average bed occupancy rate was 51.33%. The 51.4% of the patients in medical wards except paediatrics ward were of the age >50 years; the mean age was 45 years and standard deviation±6.4 years. Mean age in paediatrics was 3.89 years and standard deviation of±0.8 years. 55.1% patients had infectious diseases. The 32.7% patients stayed in hospital for up to 3 days showing significant association between nature of diseases and duration of stay (p=0.03). There was male preponderance, i.e., 54.2% males against 45.8% females. Showing significant association between gender and length of stay (p=0.01). Conclusions: Bed occupancy rate and average stay in hospital were found within recommended range; more improvement may be brought by doing further research on this issue. Keywords: Bed occupancy, Length of stay, gender, tertiary care hospital